1972
DOI: 10.3758/bf03212675
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of auditory monitoring performance in blind subjects with that of sighted subjects in light and dark

Abstract: Two experiments were performed in which blind Ss, sighted Ss working in the dark, and sighted Ss working in the light were compared as to their efficiency on an auditory watchkeeping task. Absolute and differential auditory thresholds were measured in both experiments, and in the second experiment the groups also underwent a signal detection session under alerted conditions. There was some inconsistency as to relative performance of the sighted groups, but in both experiments the blind Ss were superior on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

1978
1978
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…Finally, the superior overall performance of the deaf in relation to the hearing/prize group indicates that a greater level of extrinsic motivation was not the basis for the superior performance of the deaf observers. All in all, it appears that the present results point to a hearing-lossanalog to Benedetti and Loeb's (1972) earlier finding in regard to loss of vision. Just as blind listeners show enhancement in the quality of sustained auditory attention, deaf observers show enhancement in the quality of sustained visual attention.…”
Section: Resultssupporting
confidence: 49%
See 1 more Smart Citation
“…Finally, the superior overall performance of the deaf in relation to the hearing/prize group indicates that a greater level of extrinsic motivation was not the basis for the superior performance of the deaf observers. All in all, it appears that the present results point to a hearing-lossanalog to Benedetti and Loeb's (1972) earlier finding in regard to loss of vision. Just as blind listeners show enhancement in the quality of sustained auditory attention, deaf observers show enhancement in the quality of sustained visual attention.…”
Section: Resultssupporting
confidence: 49%
“…Benedetti and Loeb (1972) have established that loss of vision (blindness) can be associated with enhancement in the quality of auditory vigilance. The present study demonstrates that loss of hearing (deafness) can result in an analogous enhancement with regard to visual vigilance.…”
mentioning
confidence: 99%
“…Paradoxically, sensory impairment has been found to be a beneficial factor in vigilance performance. Benedetti and Loeb (1972) have reported that blind observers performed more effectively than sighted observers on an auditory vigilance task and Dittmar et al (1982) found superior performance for deaf as compared to normal hearing observers on a visual vigilance task. The utility of these findings for the selection issue is limited, however, by the availability and acceptance of blind and deaf observers for monitoring assignments in operational environments such as military surveillance, airport security, or medicine.…”
Section: Sensory Acuity and Aptitude Measuresmentioning
confidence: 97%
“…' The method of heteromodal stimulation has been used most often to study the effects of auditory stimulation on visual signal detection (Davenport, 1974;Klayman, 1973aKlayman, , 1973bMaloney & Welch, 1972;Maruyama, 1959;McGrath, 1963;Taylor, 1974;Watkins, 1964;Watkins & Feehrer, 1965) and of visual stimulation on auditory signal detection (Klayman, 1973a;McGrath, 1963;Taylor, 1974). The comments below are directed specifically toward these efforts, although they are equally applicable to other studies utilizing heteromodal stimulation (e.g., Benedetti & Loeb, 1972;Bross, 1979;Bross & Zubek, 1975;Lewkowicz & Turkewitz, 1981;Zubek, 1969).…”
Section: The Methods Of Heteromodal Stimulationmentioning
confidence: 99%
“…Meaningful auditory stimuli can induce arousal, thus helping to reduce or delay this performance decrement. Indeed, an apparent crossmodal effect in a vigilance task may disappear if observers are alerted prior to the presentation of the heteromodal signal (Benedetti & Loeb, 1972).…”
Section: The Methods Of Heteromodal Stimulationmentioning
confidence: 99%